Neuroreductionism about sex and love - Earp, B; Savulescu, J (Cambridge University Press, 2014)
"Neuroreductionism" is the tendency to reduce complex mental phenomena to brain states, confusing correlation for physical causation. In this paper, we illustrate the dangers of this popular neuro-fallacy, by looking at an example drawn from the media: a story about "hypoactive sexual desire disorder" in women. We discuss the role of folk dualism in perpetuating such a confusion, and draw some conclusions about the role of "brain scans" in our understanding of romantic love.